Wpływ działalności rolniczej na degradację i dewastację gleb - Owczarek, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Research was conducted to analyses the agricultural activity and its influence on the degradation and devastation of the soil's natural environment. The forecast describes area of lands which are devastated or degradated and their requirements to be reclaimed and developed, and shows those which are already reclaimed and developed across the territory of Poland. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 171-177